2019
DOI: 10.5858/arpa.2018-0603-cp
|View full text |Cite
|
Sign up to set email alerts
|

Bethesda 2014 Implementation and Human Papillomavirus Primary Screening: Practices of Laboratories Participating in the College of American Pathologists PAP Education Program

Abstract: Context.— Cervical cancer screening laboratory practices may evolve with new terminology and technologies. Objective.— To investigate changes in cervical cytopathology practice resulting from the 2014 Bethesda System updates and screening technologies. Design.— Questionnaires accompanied 2016 and 2017 mailings of the College of American Pathologists PAP Education program. Results.— In 2016, most laboratories surveyed had adopted or were planning to adopt 2014 Bethesda System updates, and the majority (53%; 365… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…40,000 research subjects were recruited exclusively from the cervical cancer high-risk Jiexiu and Yangqu counties in Shanxi province within six months period. Overall abnormal cytological results was 6.76% (2702/40,000), including 5.76% (2304/40,0000) reported ASC-US, which was higher but consistent with the benchmark data of most recent College of American Pathologist survey (median rate: 5.6%; range: 1.1-13.3%) [17] . The total reporting rate of combined ASC-H, LSIL, HSIL, AGC and SCCa was 1.01%, much lower than 7.1% reported by Pan et al [11] .…”
Section: Cytology Reporting Rates Differ In Yangqu County and Jiexiu supporting
confidence: 80%
See 1 more Smart Citation
“…40,000 research subjects were recruited exclusively from the cervical cancer high-risk Jiexiu and Yangqu counties in Shanxi province within six months period. Overall abnormal cytological results was 6.76% (2702/40,000), including 5.76% (2304/40,0000) reported ASC-US, which was higher but consistent with the benchmark data of most recent College of American Pathologist survey (median rate: 5.6%; range: 1.1-13.3%) [17] . The total reporting rate of combined ASC-H, LSIL, HSIL, AGC and SCCa was 1.01%, much lower than 7.1% reported by Pan et al [11] .…”
Section: Cytology Reporting Rates Differ In Yangqu County and Jiexiu supporting
confidence: 80%
“…The total reporting rate of combined ASC-H, LSIL, HSIL, AGC and SCCa was 1.01%, much lower than 7.1% reported by Pan et al [11] . Likewise, AGC rate of both Yangqu and Jiexiu counties was only 0.03% (10/40,000), much lower than AGC rate in CAP survey in US population (median rate: 0.2%, range: 0-1%) and also lower than that of recent nationwide survey in China (median rate: 0.05%; range: 0-1%) [17,18] . Similarly, Pan et al analyzed patients of community setting from other areas of Shanxi Province and reported 0.2-0.8% AGC rate, in which authors drew the conclusion of low incidence rate of cervical adenocarcinoma in Shanxi women population [11] .…”
Section: Cytology Reporting Rates Differ In Yangqu County and Jiexiu mentioning
confidence: 56%
“…Two primary HPV tests are FDA‐approved specifically for primary screening in the United States. As of 2017, primary HPV testing was available only in a limited number of US laboratories, 134 and it may take time and financial resources for laboratories currently using other HPV testing platforms to add platforms using the tests approved for primary screening 135 …”
Section: Clinical Considerationsmentioning
confidence: 99%
“…Since 2012, several RCTs have been published on the effectiveness of primary HPV testing for cervical cancer screening that include subsequent rounds of screening, 43 and there are now FDA‐approved tests for primary screening. Although the FDA approved the first test for primary HPV screening in 2014, as of 2017, only 40.6% percent of laboratories reported that they offered primary HPV screening, and, among those that did, primary HPV screening was a very small fraction of all HPV‐associated testing 134 . Furthermore, the survey reported variability in the settings where HPV genotyping (for management of positive results, not primary HPV screening) was available.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation